A novel air-dried multiplex high-resolution melt assay for the detection of extended-spectrum β-lactamase and carbapenemase genes. (December 2021) - Cubas-Atienzar, Ana I.; Williams, Christopher T.; Karkey, Abhilasha; Dongol, Sabina; Sulochana, Manandhar; Rajendra, Shrestha; Hobbs, Glyn; Evans, Katie; Musicha, Patrick; Feasey, Nicholas; Cuevas, Luis E.; Adams, Emily R.; et al.
Highlights: Development and evaluation of a novel air-dried HRM assay to detect eight major ESBL and carbapenemase genes. Sensitivity and specificity of the air-dried HRM assay versus the reference molecular tests was 94.7–98.3% and 98.5–99.2%. Assay had overall agreement of 91.1% in predicting phenotypic resistance to cefotaxime and meropenem in Enterobacteriaceae. Cross-platform validation showed almost perfect reproducibility in five different qPCR platforms. No loss of sensitivity was observed after 8 months of storage at room, refrigerator and oven temperatures. ABSTRACT: Objectives: This study aimed to develop and evaluate a novel air-dried high-resolution melt (HRM) assay to detect eight major extended-spectrum β-lactamase (ESBL) ( bla SHV and bla CTX-M groups 1 and 9) and carbapenemase ( bla NDM, bla IMP, bla KPC, bla VIM and bla OXA-48-like ) genes that confer resistance to cephalosporins and carbapenems. Methods: The assay was evaluated using 439 DNA samples extracted from bacterial isolates from Nepal, Malawi and the UK and 390 clinical isolates from Nepal with known antimicrobial susceptibility. Assay reproducibility was evaluated across five different real-time quantitative PCR (qPCR) instruments [Rotor-Gene® Q, QuantStudio TM 5, CFX96, LightCycler® 480 and Magnetic Induction Cycler (Mic)]. Assay stability was also assessed under different storage temperatures (6.2 ± 0.9°C, 20.4 ± 0.7°C and 29.7 ± 1.4°C) at six time points over 8 months. Results: The sensitivity and specificity (with 95% confidence intervals) for detecting ESBL and carbapenemase genes was 94.7% (92.5–96.5%) and 99.2% (98.8–99.5%) compared with the reference gel-based PCR and sequencing and 98.3% (97.0–99.3%) and 98.5% (98.0–98.9%) compared with the original HRM wet PCR mix format. Overall agreement was 91.1% (90.0–92.9%) when predicting phenotypic resistance to cefotaxime and meropenem among Enterobacteriaceae isolates. We observed almost perfect inter-machine reproducibility of the air-dried HRM assay, and no loss of sensitivity occurred under all storage conditions and time points. Conclusion: We present a ready-to-use air-dried HRM PCR assay that offers an easy, thermostable, fast and accurate tool for the detection of ESBL and carbapenemase genes in DNA samples to improve antimicrobial resistance detection.